2018
DOI: 10.1371/journal.pone.0202254
|View full text |Cite
|
Sign up to set email alerts
|

Traits influence detection of exotic plant species in tropical forests

Abstract: Detecting exotic plant species is essential for invasive species management. By accounting for factors likely to affect species’ detection rates (e.g. survey conditions, observer experience), detectability models can help choose search methods and allocate search effort. Integrating information on species’ traits can refine detectability models, and might be particularly valuable if these traits can help improve estimates of detectability where data on particular species are rare. Analysing data collected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…Understanding factors that influence P is useful for guiding survey design because optimal survey techniques have a high and consistent probability of detecting the target species and low sampling error (Thompson et al 1998;Williams et al 2002). Although few studies assess factors that influence detectability of plants, traits such as color, flowering time, leaf size, height, and observer ability can influence the detection process (Chen et al 2013;Garrard et al 2013;Junaedi et al 2018). We found that detectability during DS was explained by variation in soil substrate size, with lower detectability on rockier soils.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Understanding factors that influence P is useful for guiding survey design because optimal survey techniques have a high and consistent probability of detecting the target species and low sampling error (Thompson et al 1998;Williams et al 2002). Although few studies assess factors that influence detectability of plants, traits such as color, flowering time, leaf size, height, and observer ability can influence the detection process (Chen et al 2013;Garrard et al 2013;Junaedi et al 2018). We found that detectability during DS was explained by variation in soil substrate size, with lower detectability on rockier soils.…”
Section: Discussionmentioning
confidence: 79%
“…Distance sampling has been used successfully to assess abundance and detection probability (P) in animal systems, often at much larger spatial scales than that considered here (Thomas et al 2002(Thomas et al , 2010Buckland et al 2015;Roberts et al 2016). To our knowledge, however, this study represents just its eighth application in a plant system (Marsden and Pilgrim 2003;Buckland et al 2007;Crase et al 2010;Jensen and Meilby 2012;Kissa and Sheil 2012;Schorr 2013;Phama et al 2014;Junaedi et al 2018), and is the first to compare estimates from DS with what we assumed were parametric values of abundances from intensive censuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jenis tersebut juga telah dianggap sebagai salah satu tumbuhan invasif di kawasan hutan di Indonesia, yaitu TNGGP dan kawasan hutan di Sumatera Utara (Tjitrosoedirdjo et al, 2016). Meskipun demikian, dalam sejumlah studi terkini mengenai jenis tumbuhan invasif di kawasan KRC dan sekitar kawasan TNGGP (Mutaqien et al, 2011;Zuhri & Mutaqien, 2013;Junaedi, 2014;Junaedi et al, 2018), jenis tersebut luput dari perhatian. Oleh karena itu, penelitian ini bertujuan memberikan informasi persebaran populasi dan karakteristik habitat dari C. Scandens di kawasan KRC dan TNGGP.…”
Section: Pendahuluanunclassified
“…Kondisi tersebut dapat memberikan dampak negatif terhadap ekosistem yang berada di sekitarnya, seperti yang ditemukan pada tumbuhan pemanjat lainnya (Hu & Li, 2014). Selain itu, rapatnya vegetasi C. quadringularis dan keberadaan jenis invasif lainnya (Mutaqien et al, 2011;Wahyuni & Tjitrosoedirdjo, 2013;Junaedi, 2014;Damayanto & Muhaimin, 2017;Tjitrosoedirdjo et al, 2016;Junaedi et al, 2018), menjadi hambatan dalam pengendalian C. scandens lebih lanjut.…”
Section: Pembahasanunclassified